Presynaptic Modulation of Ia Afferents in Young and Old Adults When Performing Force and Position Control - Baudry, Stephane; Maerz, Adam H; Enoka, Roger M (Journal of neurophysiology, 2010)
Department of Integrative Physiology, University of Colorado, Boulder, Colorado Submitted 14 September 2009; accepted in final form 23 November 2009 ABSTRACT The present work investigated presynaptic modulation of Ia afferents in the extensor carpi radialis (ECR) when young and old adults exerted a wrist extension force either to support an inertial load (position control) or to achieve an equivalent constant torque against a rigid restraint (force control) at 5, 10, and 15% of the maximal force. H reflexes were evoked in the ECR by stimulating the radial nerve above the elbow. A conditioning stimulus was applied to the median nerve above the elbow to assess presynaptic inhibition of homonymous Ia afferents (D1 inhibition) or at the wrist (palmar branch) to assess the ongoing presynaptic inhibition of heteronymous Ia afferents that converge onto the ECR motor neuron pool (heteronymous Ia facilitation). The young adults had less D1 inhibition and greater heteronymous Ia facilitation during the position task (79 and 132.1%, respectively) compared with the force task (69.1 and 115.1%, respectively, P < 0.05). In contrast, the old adults exhibited no difference between the two tasks for either D1 inhibition ( 72%) or heteronymous Ia facilitation ( 114%). Contraction intensity did not influence the amount of D1 inhibition or heteronymous Ia facilitation for either group of subjects. The amount of antagonist coactivation was similar between tasks for young adults, whereas it was greater in the position task for old adults ( P = 0.02). These data indicate that in contrast to young adults, old adults did not modulate presynaptic inhibition of Ia afferents when controlling the position of a compliant load but rather increased coactivation of the antagonist muscle. Address for reprint requests and other correspondence: S. Baudry, Dept. of Integrative Physiology, University of Colorado, Boulder, CO 80309-0354 (E-mail: stephane.baudryatcolorado.edu ).